Barriers to the Implementation of Smart Projects in Rural Areas, Small Towns, and the City in Brno Metropolitan Area - Ševčík, Michal; Chaloupková, Markéta; Zourková, Ilona; Janošíková, Lenka (De Gruyter Open Ltd., 2022)
The implementation of smart projects can contribute to solving the current development problems of municipalities and cities of varied sizes. Although the concept of smart development is a vague term in the literature, in practice it refers to projects based on the use of modern technologies, to improve the quality of life considering economic, social, and environmental dimensions. However, not all local governments in the Czech Republic implement smart projects, even though the smart city concept is currently receiving considerable attention from national governments and from the European Union. This paper characterizes the perception of barriers to the implementation of smart projects from the perspective of fifteen representatives and officials of local governments located in the Brno Metropolitan Area in the Czech Republic. The research was conducted using semi-structured interviews with these fifteen territorial actors. It was found that the barriers to the implementation of smart projects are related to internal factors in the municipalities, such as the lack of interest of municipal leaders and officials or potential technical complications accompanying the implementation of projects. However, external factors such as the Czech government's vague grasp of the smart cities concept or cyber threats also play a role. Perceived barriers were categorized according to their type and schematized.
Keywords: smart city; smart project barriers; rural areas; metropolitan area